Risk factors for infections after endoscopic retrograde cholangiopancreatography (ERCP): a retrospective cohort analysis of US Medicare Fee-For-Service claims, 2015–2021. Issue 9 (9th September 2022) - Hutfless, Susan; Shiratori, Yasutoshi; Chu, Daniel; Liu, Simon; Kalloo, Anthony
Abstract : Objective: Contaminated reprocessed duodenoscopes pose a serious threat to patients in the endoscopy unit. Despite manufacturer changes to reprocessing guidelines, 20% of reprocessed duodenoscopes meet criteria for quarantine-level contamination based on microbiological or ATP testing. We aimed to examine risk factors for postendoscopic retrograde cholangiopancreatography (ERCP) infection. Design: Retrospective cohort analysis. Setting: US Medicare Fee-For-Service claims (2015–2021) and all-payer data (2017). Participants: In the Medicare data, 823 575 ERCP procedures were included. The all-payer five-state data, 16 609 procedures were included. Interventions: ERCP was identified by Current Procedural Terminology and International Classification of Disease (ICD) procedure codes. We identified inpatient infections using ICD diagnosis codes. Outcome measures: A logistic regression model predicted risk factors for infections occurring within 7-day and 30-day periods following ERCP. 7-day and 30-day all-cause hospitalisations and post-ERCP pancreatitis were also examined. Results: Post-ERCP infection occurred within 3.5% of 7-day and 7.7% of 30-day periods in Medicare. Disposable duodenoscopes were billed in 711 procedures, with 1.4% (n=10, 7-day) and 3.5% (n=25, 30-day) post-ERCP infections. Urgent ERCPs were the strongest risk factor for infections in the 7-day period (OR 3.3, 95% CI 3.2 to 3.4). Chronic conditions, sex (male), age (older) and race (non-white) were also risk factors. In the all-payer five-state data, fewer infections (2.4%, 7 days) were observed. No difference arose between Medicare and other payers for 7-day period infections (OR 1.0, 95% CI 0.7 to 1.3). Conclusions: Urgent ERCPs, patient chronic conditions and patient demographics are post-ERCP infection risk factors. Patients with infection risk factors should be targeted for specialised infection control prevention measures, including disposable duodenoscopes.